Efektivitas Media Scrapbook Untuk Pengkungkapan Emosi Negatif Peserta Didik - Wisma Dwiana Anograh; Veny Iswantningtyas; Anisyah Anisyah (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Sample The purpose of this study was to determine the effectiveness of classical guidance services with scrapbook media to spread negative emotions. In the development stage, conveying emotions is very important so that its development is not hampered where this scrapbook media will help students in spreading their emotions. Where the application in this study will use classical guidance services that will be carried out in class XI-7 of SMA Negeri 2 Kediri. from the results of the pretest and the posttest. Where in the pretest in the low category column there were 06 students to 0 students, in the medium category column with the number of students 26 to 20, and in the high category column there were 05 students to 16 students, it can be concluded that classical guidance services with scrapbook media can help reveal negative emotions of students.